Tourism Management through Sapta Pesona Concept to Increase Tourist Attraction in Timpag Village, Tabanan Regency - Laksmi, Putu Ayu Sita; Yogiarta, I Made; Rustini, Ni Made (Institut Pariwisata dan Bisnis Internasional, 2023)
The tourism potential of the Timpag village has not been managed properly so that it has not produced maximum results in the tourism sector. This study aims to see the tourism management of Timpag Village through the concept of Sapta Pesona. This study uses a qualitative approach with data analysis techniques are descriptive analysis. Data collection techniques are by previous research studies and observations. The results showed that Timpag Village has a lot of tourism potential that can be developed, namely Undagi Village Farmer, there are purification sites (pelukatan), breeding huts, Celemanik View, Pondok Uma urip, Telaga Tunjung Dam, Titi Empag River Tubing, Cycling, and artificial tourism weeding culture in Bali typical of Timpag Village. The community's efforts in carrying out sapta pesona in Timpag Village have been in the category very well. The elements of Sapta Pesona are safe, orderly, clean, cool, beautiful, friendly, and memorable. This can be created by the community itself by always keeping their village safe from crime and violence and of course supported by the local Babinsa. However, there is no information on the Timpag Village Map that has not been installed, some areas such as parking lots have not been paved, and there are still local people who have motorbikes using noisy exhaust which results in a little noise in the area.